Chronic obstructive pulmonary disease in patients with stable heart failure: Prevalence and associated factors - Mbatchou Ngahane Bertrand Hugo; Che Vanessa Lum; Abinkeng Tazifua Ebenezer; Dzudie Anastase; Ngote Roger; Kamdem Felicité; Mandengue Samuel Honoré (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is characterized by irreversible airflow limitation in the lungs. COPD frequently coexist with Heart Failure (HF) but most patients go undiagnosed because of similarity of symptoms. Data on prevalence of COPD in HF are discrepant and scarce. In addition, associated factors of COPD in these patients have not been completely investigated. Our objectives were to determine the prevalence of COPD amongst stable HF patients and to identify the factors associated. Methods: It was a cross-sectional study carried out from January 2016 to April 2016 at the Douala General Hospital. All stable HF patients 40 years and over who came for routine follow-up and who met up inclusion criteria were enrolled. A questionnaire was used to obtain information on pulmonary symptoms, risk factors, sociodemographic data, comorbidities and spirometric measurements. COPD was defined by airflow limitation which corresponds to the ratio of post-broncho dilation forced expiratory volume in one second on the forced vital capacity less than 70% (FEV1/FVC<70%). SPSS20 software was used for data analysis and a P-value <0.05 was considered significant. Results: A total of 86 HF patients were included in our study. The median age was 66.5 years with an Interquartile Range (IQR) of 57-75years. Female sex was the most represented (53.3%). Twenty-two patients had COPD giving a prevalence of COPD in HF of 25.6% (95%CI; 16-34). Sputum production was significant in those with COPD (p= 0.012) and elderly age (≥65 years) was associated with COPD (p= 0.026). Conclusion: Our findings suggest that one out of four patients diagnosed with heart failure has chronic obstructive pulmonary disease with sputum production being the most likely symptom and elderly age an associated factor of having COPD in heart failure. Clinicians should think of an associated COPD when investigating patients with heart failure.